A Comparative Analysis of Glycemic Indices in Predicting Outcomes Following Aneurysmal Subarachnoid Hemorrhage. (16th November 2020) - McIntyre, Matthew; Halabi, Mohamed; Li, Boyi; Long, Andrew; Van Hoof, Alexander; Afridi, Adil; Gandhi, Chirag D; Schmidt, Meic H; Cole, Chad D; Santarelli, Justin; Al-Mufti, Fawaz; Bowers, Christian A
Abstract: INTRODUCTION: While hyperglycemia is associated with worse outcomes following aneurysmal subarachnoid hemorrhage (aSAH), there is no consensus on the optimal glucose control metric, acceptable in-hospital glucose ranges, or suitable insulin regimens in this population. METHODS: This is a four-year retrospective cohort study of patients who presented with aSAH. Hospital insulin use, admission glucose, as well as hospital glucose mean (MHG), minimum (MinG), maximum (MaxG), and variability were all assessed. Primary endpoints were mortality, complications, and angiographic vasospasm. Univariate and stepwise multivariate analysis were performed to determine predictors of, and optimal cutoffs for, primary endpoints. RESULTS: Of the 217 patients identified, the majority were white (122/217, 56.2%), women (142/217, 65.4%) with an average age of 57.6 ± 1.0 years and Hunt & Hess score of 2.9 ± 0.1. Complications occurred in 83 (38.2%) patients, 124 (57.1%) had vasospasm, and 41 (18.9%) died. MHG independently predicted ( P < . 001) mortality and MaxG independently predicted complications ( P = . 017) while lower MinG independently predicted ( P = . 015) vasospasm in multivariate analysis. Patients with MHG ≥ 140mg/dL had 10 times increased odds of death [odds ratio (OR) = 10.3; P < . 0001] while those with a MinG ≤ 90mg/dL had nearly double the odds of vasospasm (OR = 1.8; P = . 0422). Inpatient insulin therapy was associated with increased complications (OR = 2.1; P = . 0136) and provided no mortality benefit. However, for patients with an MHG ≥ 140 mg/dL, insulin therapy resulted in lower mortality (OR = 0.3; P = . 0358), higher vasospasm (OR = 5.3; P = . 0067), and no increased complication risk. CONCLUSION: Elevated MHG and MaxG are highly predictive of poorer outcomes following aSAH. Conversely, lower MinG is associated with increased vasospasm risk. We suggest that future SAH insulin therapy trials consider targeting glucoses between 90 and 140mg/dL and initiate insulin therapy based on MHG, rather than other hyperglycemia measures.